Genome phylogenetic analysis of Brucella melitensis in Northwest China - Xiaoan Cao; Ping Liu; Jinyan Wu; Zhijie Liu; Yuling Zhang; Cai Yin; Lan Ying; Jinrui Ma; Jijun He; Youjun Shang; Rui Du; Zhiguo Liu; et al. (BMC Microbiology)
Abstract Brucellosis poses a severe threat to public health in Northwest China; however, the genome phylogeny and transmission pattern of Brucella melitensis from sheep and yaks in this region remain unclear. In this study, bacteriology, conventional biototyping, and whole-genome single-nucleotide polymorphism (WGS-SNP) were applied to depict the phylogenetic profiles of strains from Northwest China. A total of 46 Brucella strains were identified as B. melitensis bv. 3, which was isolated from at least three animal (livestock and wildlife) hosts, implying that B. melitensis infection is prevalent in the Northwest and suggesting that host diversity provides an optimal niche for the spread and maintenance of B. melitensis in this region. WGS-SNP analysis divided the 46 B. melitensis strains into four clades (C-I–IV) that harbored eight SNP genotypes (STs), implying that at least four lineages are prevalent in the Northwest. Global WGS-SNP phylogenetic analysis of strains revealed that all Northwest strains belong to genotype II. Strains from different clades presented high genetic similarity with strains previously collected from the Northwest. This study provides robust evidence supporting the notion that multiple similar B. melitensis lineages are persistently prevalent in human populations and animals in the Northwest. The economic development of animal husbandry has accelerated the cross-regional flow of livestock and livestock products, driving the spread and reach of the disease. Therefore, tailoring a targeted control strategy is necessary to counter the current serious epidemic trend.